Antitrust between success and failure: A sociological and ethnographic reappraisal of Brazilian competition policy - Iagê Miola; Gustavo Onto (economic sociology. perspectives and conversations, 2024)
Market concentration, alongside financialization and the climate crisis, is increasingly perceived as a major problem in contemporary capitalism. The fact that significant economic sectors are in the hands of a small number of powerful corporations - a phenomenon that is epitomized by Big Tech domination of the "digital economy" - is causing widespread concern. Excessively concentrated markets can be dysfunctional for the competitive logic that underlies them, as well as for consumers and for small and medium-sized companies, whose very survival is threatened. That in turn aggravates existing social and economic inequalities and may even undermine established democratic structures, for example through the conversion of economic power into political power.
Keywords: 300